2017
DOI: 10.1109/lawp.2016.2583203
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Pattern-Reconfigurable Bended Horn Antenna for High-Power Applications

Abstract: International audienceIn this letter, a mechanically pattern-reconfigurable antenna is presented to achieve various half-power beamwidth for high-power applications. A bended H-sectoral horn antenna with two movable metallic flaps is presented to change the aperture length in the H-plane direction in order to provide reconfigurable half-power beamwidth starting from 58.7° to 16.5°. Moreover, the horn radiating aperture is integrated into a corrugated ground plane to increase the E-plane radiation pattern gain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…This antenna provides only four beams with the requirement of complex feeding network due to the requirement of phase modulation. In Reference , a bent H‐sectoral horn antenna is reported wherein the reconfigurable half‐power beamwidth is obtained by mechanically changing the aperture length with the two movable metallic flaps. This antenna is limited by its size due to the requirement of multiple elements and corrugated ground surfaces to achieve higher gain.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…This antenna provides only four beams with the requirement of complex feeding network due to the requirement of phase modulation. In Reference , a bent H‐sectoral horn antenna is reported wherein the reconfigurable half‐power beamwidth is obtained by mechanically changing the aperture length with the two movable metallic flaps. This antenna is limited by its size due to the requirement of multiple elements and corrugated ground surfaces to achieve higher gain.…”
Section: Introductionmentioning
confidence: 53%
“…It is found that the highest efficiency of an antenna is 83%, and 81% for the range of 2.4‐2.66 and 3.31‐3.57 GHz, respectively. Larger bandwidth coverage of 270 and 360 MHz at 2.4‐ and 3.5‐GHz band, respectively, when compared to a narrow operating bandwidth of fewer than 200 MHz was reported in References , , , and The efficiency reported in this research work is 83% which is higher than the efficiency reported in References , , , , and . A total of 16 different beams are produced by the proposed antenna with reduced complexity; however, the research work reported in References and gives a maximum of eight beams with increased numbers of active elements and patches. The maximum gain achieved by this antenna is 10.7 and 9.8 dBi at 2.4‐ and 3.5‐GHz band, respectively; however, the maximum gain reported in References , , , , and are less than 9 dBi. The design of antennas integrating multiple features, such as high gain, multiband, wide bandwidth, directive radiation, multiple radiation patterns for omnicoverage, low cost, and less complex structure, is of increasing demand for vehicular communication. This antenna satisfies all these requirements by using low‐cost FR4 dielectric material as substrate for reducing manufacturing cost, the multiple radiation patterns are realized from simple multiport excitation technique, high gain is attained by etching dual SR slots at the ground plane with the addition of reflector and hence this antenna is useful for high throughput satellite as well as base station‐enabled data services. …”
Section: Measurement Resultsmentioning
confidence: 99%
“…With the development of wireless techniques, antenna is a key component for the wireless application . Horn antennas have been always gratefully popular due to their characteristics of high gain, wideband, stable and all‐meta structure, easy to be integrated in the array antennas . In Reference , a wideband low‐profile substrate integrated waveguide H‐plane horn antenna mounting on a large conducting cylinder is presented.…”
Section: Introductionmentioning
confidence: 99%
“…And a compact‐size and high‐directivity horn lens antenna for millimeter‐wave application is presented in Reference . Meanwhile, bended horn antenna to achieve pattern‐reconfigurable is used for high‐power application in Reference . Most of them are designed for the linear polarized antennas.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in [5], the authors proposed a solution based on a coupled three-slot array. This solution is limited in term of choosing inter-element distance (typically 0.75λ).…”
Section: Introductionmentioning
confidence: 99%